P005 Cytokine mediated intercellular communication in inflammatory bowel disease. (27th May 2021) - Thomas, J P; Olbei, M; Hautefort, I; Modos, D; Korcsmaros, T
Abstract: Background: During inflammatory bowel disease the mucosal immune system is altered. The mucosal immune cells are communicating through the various cytokines. Single cell and small volume RNA-seq and proteomics approaches make the investigation of cytokine networks plausible However the lack of specific resources make such efforts hard. Methods: To address this need in this project, we built a cell-cell communication map, CytokineLink, which collates cytokine mediated intercellular interactions. CytokineLink collects the cytokine-cytokine receptor interactions from the OmniPath, immuneXpresso and immunoGlobe databases. We demonstrate the applicability of CytokineLink by presenting how cytokine feedback loops are built and altered during Ulcerative Colitis. We mapped single-cell RNA-seq expression data from inflamed and uninflamed Ulcerative Colitis biopsies to the interactions between cytokines and cytokine receptors, and then we compared the specific cytokine-mediated cell-cell interactions. Results: Using our approach, we were able to point out major differences in cell-cell communication between inflamed and uninflamed conditions, and identify key cytokine changes. For example, the generally anti-inflammatory cytokine IL-10 is produced by regulatory T-cells in both conditions. However the IL-10 receptor positive cells are altered between the inflamed and uninflamed condition: dendritic cells and innate lymphocytes did not express the receptor in the sufficient amount. It suggests that not the cytokine level directly but the receptor level alterations are involved in ulcerative colitis. Also the chemokine CXCL12 was expressed by the inflammatory fibroblasts. This cytokine promotes the T-cell recruitment and through that inflammation. Conclusion: With CytokineLink, researchers are capable to pinpoint the most important interactions in the changing mucosal immune system and propose novel therapeutic approaches. We are currently developing a website and easy to follow workflows to make CytokineLink available.